Ant Colony Method to Minimize Single Machine Scheduling Problem - .M Araibi, Sami (University of Thi-Qar Journal of Science, 2019)
The study deal with a single machine scheduling problem where the objective is to find the sequence which it give the optimal or efficient solution for the objective function the sum of discounted weighted completion time and number of tardy jobs. The optimal solution was found for some special cases. Ant colony optimization (ACO) using to found an approximate solution. Results of extensive computational tests show that proposed (ACO) is effective in solving problems up to (1000) jobs at a time less than or equal to (10) minutes.